Pengelolaan Royalti Hak Cipta Lagu dan Musik : Studi Kasus Pada Bisnis Karaoke - Handoko, Windy Fariskya; Roisah, Kholis (LPPM Universitas Ekasakti Padang, 2024)
Managing song and music copyright royalties is a crucial aspect in the entertainment industry, especially in the context of the increasingly growing karaoke business. This study aims to investigate song and music copyright royalty management practices in the karaoke business, with a focus on implementation and compliance with applicable copyright regulations. Through a case study approach, we analyze the strategies, policies and procedures implemented by karaoke businesses in managing royalties, as well as their impact on relations with copyright holders and the sustainability of the industry. Data was collected through in-depth interviews with karaoke business owners, copyright holders and other related parties. Our findings illustrate the challenges and opportunities faced by karaoke businesses in complying with copyright regulations, while also identifying best practices in royalty management that can improve the balance between the interests of businesses and copyright holders. The practical and theoretical implications of these findings are discussed, along with recommendations for further improvement and development in the management of song and music copyright royalties in the context of the karaoke business. It is hoped that this research will provide valuable insights for stakeholders in the entertainment industry and contribute to the literature on copyright management and business sustainability.